Assessing the exchange coupling in binuclear lanthanide(iii) complexes and the slow relaxation of the magnetization in the antiferromagnetically coupled Dy2 derivative1. Issue 7 (15th July 2015) - Chow, Chun Y.; Bolvin, Hélène; Campbell, Victoria E.; Guillot, Régis; Kampf, Jeff W.; Wernsdorfer, Wolfgang; Gendron, Frédéric; Autschbach, Jochen; Pecoraro, Vincent L.; Mallah, Talal
<x xml:space="preserve">Abstract</x> Two relaxation processes of the magnetization in an antiferromagnetically coupled Dy2 metallacrown-based complex.